The unfolding of social entrepreneurship in the context of a developing economy - De Avillez, Maria Margarida Durão (2017)
This thesis addresses how social entrepreneurship (SE) is being enacted in a developing economy as a means to promote poverty alleviation and sustainable development. Researching SE in developing economies is relevant considering the need to identify sustainable and innovative models for private sector engagement and civil society capacity building in contexts marked by resource constraints, institutional voids, and aid-dependency.